2008
DOI: 10.11606/rco.v2i2.34706
|View full text |Cite
|
Sign up to set email alerts
|

Custeio alvo: utilização do sistema de gerenciamento de lucro pelos fabricantes de veículos automotores com indústri no Brasil

Abstract: Neste trabalho são pesquisadas as indústrias automotivas com fábrica no Brasil, com o objetivo de verificar se a utilização do sistema de Custeio Alvo para planejamento de custos e lucros praticada pelas empresas é aderente à teoria. Trata-se de uma pesquisa exploratória com uso de questionário como instrumento de coleta de dados. O questionário foi elaborado com base nas etapas apresentadas por Monden (1999), que são empregadas no processo de custeio alvo pelas indústrias automotivas. Foram selecionadas 16 em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…In turn, the desired profit margin is also defined during the product design, based on short and long term strategic objectives and goals. And, the target cost represents the maximum cost of production, taking into account the target market price and the profit desired by the company (Gagne, & Discenza, 1995;Brito, Garcia, & Morgan, 2008;Ferreira, & Machado, 2015).…”
Section: Literature Review 21 Target Costingmentioning
confidence: 99%
See 3 more Smart Citations
“…In turn, the desired profit margin is also defined during the product design, based on short and long term strategic objectives and goals. And, the target cost represents the maximum cost of production, taking into account the target market price and the profit desired by the company (Gagne, & Discenza, 1995;Brito, Garcia, & Morgan, 2008;Ferreira, & Machado, 2015).…”
Section: Literature Review 21 Target Costingmentioning
confidence: 99%
“…Target costing, which is a management of costs process, should not be confused with target cost, which is one of the components and object of target costing, along with the target selling price and the desired margin of profit (Camacho, & Rocha, 2007;Brito, Garcia, & Morgan, 2008).…”
Section: Literature Review 21 Target Costingmentioning
confidence: 99%
See 2 more Smart Citations
“…In articles in Accounting and Business Administration journals published in Brazil between 2001 and 2011, research on TC addresses questions related to its concept and definition (CRUZ;COLAUTO et al, 2004), application to practice BEUREN, 2006;BIAZEBETE et al, 2009), case study and multiple cases to confirm its use (SOUZA et al, 2010a;OYADOMARI et al, 2010) and studies that investigated its use in populations of companies (RECKZIEGEL et al, 2007;ONO;ROBLES JÚNIOR, 2004;SOUZA et al, 2003;SOUZA et al, 2005;BRITO et al, 2008;OYADOMARI et al, 2008;MACHADO;SOUZA, 2006;SOUZA et al, 2010b). No studies were found, however, that related TC to some kind of factor that was able to enhance its adoption and use.…”
Section: Introductionmentioning
confidence: 99%